Different Chinese herbal medicine therapy for idiopathic thrombocytopenic purpura: A protocol for systematic review and Bayesian network meta-analysis. Issue 13 (2nd April 2021) - Chen, Wen-Ting; Tang, Rui-Mei; Huang, Ying; Pan, Yan-Ping; Wang, Shu-Wen; Wang, Gu-Yun
Abstract: Background: Idiopathic thrombocytopenic purpura (ITP) is a common immune system and blood system disease in clinical practice, and it is a hemorrhagic disease caused by immune factors causing platelet destruction and decreasing number of platelets. There is currently no effective treatment plan for ITP. At this stage, glucocorticoid and gamma globulin are mostly used in the treatment of ITP, and some patients use splenectomy to achieve therapeutic purposes, but the various treatment methods are inadequate. At this stage, a large number of randomized controlled studies have reported that Chinese herbal medicine has achieved good curative effect in the treatment of ITP. However, due to the variety of Chinese herbal medicine, there has been no evidence of the effectiveness and safety of Chinese herbal medicine in the treatment of ITP. Because of the above reasons, this study uses the network meta-analysis method based on Bayesian method to compare the clinical efficacy and safety of different kinds of Chinese herbal medicine in the treatment of ITP through direct and indirect comparison, in order to provide evidence-based medical support for the treatment of ITP with Chinese herbal medicine. Methods: This study uses the method of combining free words with theme words, and using computer to retrieve PubMed, EMbase, The Cochrane Library, WANFANG Database, CNKI, and VIP Database, etc, to collect the randomized control studies on Chinese herbal medicine in the treatment of ITP. The retrieval time is from the establishment of each database to January 2021, and the retrieval languages are Chinese and English. Two researchers independently read the title, abstract and full text of the article to determine whether it is included in the literature; In the event of a disagreement, a third researcher will join the discussion to resolve the disagreement; For the literature that lacks information, trying to contact the original author of the document to supplement it. The literature quality evaluation carried out by using the Stata 14.0 software to draw network and funnel plots, in accordance with the quality evaluation criteria of version 5.1.0 of the Cochrane System Evaluation Manual. Statistical analysis is performed by using ADDIS 1.16.8 software based on the Bayesian model. Results: This study will compare the clinical efficacy and safety of different types of Chinese herbal medicine in the treatment of idiopathic thrombocytopenic purpura through the method of network meta-analysis, and rank the different types of Chinese herbal medicine according to their effectiveness, and the results will be published in a peer-reviewed, high-quality academic journal. Conclusion: This study will find effective and safe Chinese herbal medicine for clinical treatment of ITP from the perspective of evidence-based medicine, and benefit more ITP patients.